La conducta disruptiva y su incidencia en el aprendizaje de los estudiantes de cuarto grado de la “Institución Educativa Jacinto Martín Aspiazu Peralta”, periodo lectivo 2019-2020. - Plúa Quijije, Elizabeth Jacqueline (2021)
This research work demonstrates the following problem: How does disruptive behavior affect the learning of fourth grade students from the Jacinto Martin Aspiazu Peralta Educational Institution of La Esperanza Parish ?; It is worth mentioning that the data collected was directed to the problem mentioned according to the time spent in the classroom, where disruptive behavior was identified in several students, so this investigative work focused on identifying the factors that influence this type of behavior. that affect the academic development of students, the general objective has been to develop a proposal through recreational activities that will reduce the disruptive behavior of students, diagnosing the current situation of the family of each student, the validation of the proposal and the results obtained; The methodologies applied in this work such as the analysis and compilation of information, the observation, the survey of each family member, documentary research, the comparison of the working methods within the classroom and the activities that the proposal raises; The results are presented by means of tables that more easily demonstrated the results with respect to the surveys that were carried out with the parents of families. of fourth grade to identify the factors that influence disruptive behavior. With the help of the proposal validated by specialists in the educational field, it is being possible to improve academic performance and reduce disruptive behavior.